2000
DOI: 10.1007/s004649900016
|View full text |Cite
|
Sign up to set email alerts
|

Four-year experience with pleural abrasion using a rotating brush during video-assisted thoracoscopy

Abstract: VATS combined with mechanical brush pleurodesis using the electrical brush system is a highly effective and safe treatment for patients with recurrent primary spontaneous pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…The brush system, when combined with VATS, was shown to be a highly effective and safe treatment for SP. The drainage time, hospitalization time and recurrence rate are comparable with other forms of pleurodesis in VATS (34).…”
Section: Vats In Spontaneous Pneumothoraxsupporting
confidence: 49%
“…The brush system, when combined with VATS, was shown to be a highly effective and safe treatment for SP. The drainage time, hospitalization time and recurrence rate are comparable with other forms of pleurodesis in VATS (34).…”
Section: Vats In Spontaneous Pneumothoraxsupporting
confidence: 49%
“…Recent reports have also shown that additional pleurodesis reduces the postoperative recurrence rates of pneumothorax [1,5,12,13,16]. Reported recurrence rates are 0% (n = 0/33; follow-up range, 36±54 months) for apical pleurectomy [1], 0.5% (n = 1/195; follow-up range, 2±72 months) to 2.9% (n = 1/34; follow-up range, 1±12 months) for talc poudrage [5,16], 2.1% (n = 1/47; follow-up range, 20±56 months) for pleural abrasion using a rotating brush [13], 4% (n = 1/24; follow-up range, 36±58 months) for acromycin injection [12], and 5.0% (n = 2/40) for subtotal pleurectomy [5]. Compared with these techniques, our electrocautery procedure was equally as eective in preventing postoperative recurrences.…”
Section: Discussionmentioning
confidence: 96%
“…Because ruptured blebs are mostly confined to the upper lobe, mechanical pleurodesis such as that used in this technique might be sufficient to obliterate the upper lung fields. Horio et al and Maier et al also showed satisfactory results with limited mechanical pleurodesis, however apical partial pleurectomy alone will not prevent recurrence in the lower part of the chest [7,17]. If complete apical pleurectomy by abrading the lower parietal pleura is performed, the recurrence rate is significantly reduced [12].…”
Section: Discussionmentioning
confidence: 99%